Analisis Manajemen Persediaan Beras pada Perusahaan Umum Badan Urusan Logistik (Bulog) Kabupaten Mamuju - Rasyid, Rohsita Amalyah; Kamarudin, Jamaludin; Suwanti, Suwanti (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
ABSTRACK Analysis of Rice Inventory Management in Public Company Logistics Affairs Agency (Bulog) Mamuju Branch The General Company of the Logistics Affairs Agency (Bulog) of the Mamuju Branch is a State-Owned Enterprise (BUMN) in charge of maintaining food stability in Mamuju district. The General Company Office of the Mamuju Branch of the Logistics Affairs Agency, which carries out the duties as a food safety guard, has 15 employees. The problem that appears in the General Company of the Mamuju Branch of Logistics Affairs is in its distribution, such as where the lack of distribution to consumers results in long stored rice stocks which result in rice damage so that it can harm the company itself. This study aims to confirm the analysis of rice inventory management at the General Logistics Affairs Agency (Bulog) Mamuju Branch. The research method used is a qualitative method with primary and secondary data collection. The analytical instrument used is the analysis of Economic Order Quantity (EOQ), safety stock (Safety Stock) and Reorder Point (ROP) at the General Logistics Affairs Agency (Bulog) Mamuju Branch. Based on the results of the analysis and discussion of the data carried out, the optimal order quantity results for July-December 2021 are 52 tons and for January-June 2022 as many as 58 tons. The reorder point for July-December 2021 can be made when the remaining inventory is 33 Tons and for January-June 2022 the remaining 25 Tons. Keywords : Inventory Management and General Company Logistics Affairs Agency (Bulog) Mamuju Branch